Prinsip Pertanggungjawaban Mutlak Akibat Perbuatan Melawan Hukum Dalam Sengketa Pencemaran Lingkungan - Ardiansyah, Aldizar Fikri; Rizqathallah, Mohamad Rifqi; Saputra, Rafi Rangga; Putri, Tiara Frianita; Patricia, Zefanya; Ramadhani, Dwi Aryanti (Media Hukum Indonesia (MHI), 2024)
This research reviews the principle of strict liability resulting from unlawful acts, implemented in environmental pollution disputes. An unlawful act, as stipulated in Article 1365 of the Indonesian Civil Code (KUH Perdata), is an act that violates civil law, either contained in an agreement or not, and causes harm to third parties. However, in its application, especially in environmental law enforcement, there are weaknesses in proving the element of fault. The principle of strict liability is regulated in Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management, which means that in cases where environmental damage occurs, the defendant is absolutely responsible for the damage, regardless of intent or negligence. This research analyzes the decision of the North Jakarta District Court Number. 735/Pdt.G/2018/PN.Jkt.Utr., where PT How Are You Indonesia was found guilty of environmental pollution. According to Article 88 of Law Number 32 of 2009, those producing hazardous and toxic waste (B3) are strictly liable without the need for proof of fault. The judge granted the plaintiff's claim, declared the defendant guilty, and ordered them to pay compensation of IDR 12,198,942,574, emphasizing the importance of compliance with environmental standards and sending a strong message to other business actors.